Revestimentos e filmes biodegradáveis de deferentes amiláceas: Caracterização e aplicação pós-colheita em manga - Rodrigues, Antonio Augusto Marques (2019)
The use of biodegradable natural polymers for post-harvest food preservation is a trend consistent with society's commitments to sustainability. Among natural polymers, starch has been gaining prominence due to its great worldwide availability, high extraction yield, nutritional value, low cost, biodegradability and biocompatibility. Yam, cassava, jackfruit and mango seeds kernel have potential for starch extraction and use in the food industry or for the formulation of biodegradable coatings. Mango, a climacteric fruit, has quick ripening, requiring post-harvest technologies to increase its shelf life. The objective of this study was to characterize the physical, chemical and optical properties of mango seed kernel, jackfruit seeds, yam and cassava starches in the production of biodegradable films and coatings as well as determine the potential for application in post-harvest mango conservation. The experiments were carried out at the Embrapa Semiárido, Post-Harvest Physiology Laboratory. Four starch sources were used: jackfruit seed, mango seed kernel, yam and cassava. Starch characterizations were carried out regarding their chemical, physical and optical potential. The starches were used as coatings on the 'Palmer' mango fruit at the concentrations of 3% (cassava starch) and 3.5% (yam starch, jackfruit seed and mango seed kernel). These starches were also used for the development of biodegradable films, being prepared from three concentrations (2, 3 and 3.5%) for each of the sources. These films were submitted to physical, optical and mechanical evaluations. From these experiments, the jackfruit seed and mango seed kernel starches were selected for use as 'Tommy Atkins' mango fruit coating. The experiment was conducted in a completely randomized design, in a 7 x 6 factorial arrangement, with 7 coatings and 6 storage times. The following coatings were used mango seed kernel starch; mango seed kernel starch + chitosan; jackfruit seed starch; jackfruit seed starch + chitosan; chitosan; carnauba wax and control (uncoated). Mangos were stored under refrigeration (12.1 ± 0.2 °C and 88.9 ± 2.8% RH) for 21 days followed by 9 days at room temperature (23.3 ± 0.2 °C and 88,6 ± 2.7% RH). The four sources presented potential for starch extraction due to total starch and amylose content. The films developed presented physical, optical and mechanical characteristics comparable to commercial ones. The increase in starch concentration directly influenced the thickness, water vapor permeability, rupture stress and drilling force. The application of the tested coatings resulted in: weight loss reduction, longer green color maintenance, delayed pulp firmness loss, soluble pectin and β-carotene content increase reduction, chlorophyll a and b decrease reduction and in the α-amylase enzyme action in mango fruit. Coatings from mango seed kernel and jackfruit seeds, chitosan coatings and carnauba wax stood out for these effects.